We think you can dance! A pilot randomised controlled trial of dance for nursing home residents with moderate to severe dementia. (December 2016) - Low, L.F.; Carroll, S.; Merom, D.; Baker, J.R.; Kochan, N.; Moran, F.; Brodaty, H.
Abstract: Objectives: To evaluate the feasibility of a dance program for people with moderate to severe dementia living in nursing homeswith regards to recruitment and retention, assessment tools, intervention safety, attendance and engagement. Design: Pilot randomised controlled trial with assessments at weeks 0, 16 and 32. Setting: A nursing home in Sydney, Australia. Interventions: Experienced dance teachers conducted dance groups (intervention) or music appreciation and socialisation groups (control) for 45 min, three times a week for 16 weeks. Main outcome measures: Descriptive statistics for recruitment and retention, adverse events and attendance and engagement. Results: Recruitment was smooth, attrition was17% over 32 weeks. Engagement during the sessions was high, and no serious falls or behavioural incidents occurred. Average attendance was poorer than anticipated for dance groups (67%) in comparison to music groups (89%). A ceiling effect on the Severe Impairment Battery and the logistical challenges of the Clinical Global Impression of Change meant they may not be optimal tools. Conclusions: It is feasible to conduct a study of group dance for people with moderate to severe dementia in residential care. Choice of attention control condition should be reconsidered.